2014
DOI: 10.5812/ijb.18562
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory Impact of Peganum harmala L. on Two Breast Cancer Cell Lines

Abstract: Background: ß-carbolines, harmaline and harmine, are major alkaloids present in the seeds of Peganum harmala L. These alkaloids are known as herbal active principals with potential use in pharmaceutical and medicine. Objectives: To assess the growth inhibitory effect of phyto-alkaloids, harmaline and harmine, on cancer cell lines. Materials and Methods: P. harmala L.'s alkaloids were extracted by acidic/basic extraction method and identified by two methods, Fourier Transform Infra-Red Spectroscopy (FTIR) and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Several studies confirmed antimicrobial properties of P. harmala against different microorganisms (7,15,16). The present study showed a good antibacterial activity for P. harmala seeds extract in different concentrations against MRSA clinical strains, which is in agreement with the results of other studies from Iran by Mazandarani et al (17) and Mohsenipour et al (18).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies confirmed antimicrobial properties of P. harmala against different microorganisms (7,15,16). The present study showed a good antibacterial activity for P. harmala seeds extract in different concentrations against MRSA clinical strains, which is in agreement with the results of other studies from Iran by Mazandarani et al (17) and Mohsenipour et al (18).…”
Section: Discussionsupporting
confidence: 92%
“…In the previous study, the anti-cancer impact of P. harmala on cancer cell lines was confirmed by MTT test [18] . In the present study, the apoptosis assay was used to elucidate the anticancer effect of P. harmala ’s seed extract.…”
Section: Introductionmentioning
confidence: 78%
“…P. harmala seeds were collected from the mountains of Shahrekord, Chaharmahalo Bakhtiari province, Iran. The P. harmala ’s alkaloid extract has been prepared according to Seyed Hasan Tehrani et al [18] .…”
Section: Methodsmentioning
confidence: 99%
“…Peganum harmala has been widely used in diverse therapeutic purposes [ 42 ] as it contains several pharmacological activities, for example, anti-cancer [ 43 ], anti-oxidant [ 44 ], anti-inflammation [ 45 ], and anti-microbial activities, which included anti-viral [ 46 ], anti-bacterial [ 45 ], anti-fungal [ 47 ], and anti-parasitic [ 48 , 49 ] effects. Our study discovered the anti- Acanthamoeba activity of the P. harmala seed extract against A. triangularis .…”
Section: Discussionmentioning
confidence: 99%